Long Acting Somatostatin Analogue: Clinical Potential for Gastrointestinal Disease - Richard N. Fedorak (Canadian Journal of Gastroenterology)
Name somatostatin is found throughout the gastrointestinal tract and has a wide variety of biological actions. Nevertheless, its short biological half-life and limited stability necessitate its use via continuous parenteral infusion and, thus, limits its therapeutic usefulness The development of long acting somatostatin analogues have lead to a re-examination of the therapeutic usefulness of somatostatin in gastrointestinal disease. Somatostatin analogues appear most beneficial tn preventing symptoms associated with neuroendocrine tumours. In addition, case controlled studies exist to demonstrate somatostatin analogue effectiveness in treatment of gastrointestinal hemorrhage, pancreatic fistula, pancreatitis, short bowel syndrome and dumping syndrome.